KEDUDUKAN AKTA PEMBERIAN HAK TANGGUNGAN (APHT) DALAM AKAD JUAL BELI (BAIâ AL-MURABAHAH) PADA BANK TABUNGAN NEGARA (BTN) SYARIAH CABANG YOGYAKARTA - , Retno Hasstuti Sandyakawuri, S.H; , Yulkarnain Harahab, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to determine the position of APHT on sales and purchase agreement (Bai' Al-Murabahah) at Bank Tabungan Negara (BTN) Syariah Branch of Yogyakarta to award financing for facilities of KPR or purchase of residential houses by customers, and the settlement process of financing if there is a failure on execution of sales and purchase agreement (Bai' Al-Murabahah). This research is a juridical empirical. Empirical because of emphasis on a thorough field research and supported by the research literature to complement data obtained from field research. The data collected were analyzed qualitatively and made into form of descriptive research report. Based on the results of this research are: 1. The position of APHT on sales and purchase agreement (Bai' Al-Murabahah) at BTN Syariah Branch of Yogyakarta is the supplemental (accessoir) and contract of KPR-BTN Syariah is the principal (obligatoir). APHT serves as a warranty of finance repayment to the BTN Syariah customers Branch of Yogyakarta as a preferred creditor, if in the future the customers failed to settle KPR-BTN Syariah financing. 2. Completion of financing if there is a case of failure at execution on sales and purchase agreement (Bai' Al-Murabahah) at BTN Syariah Branch of Yogyakarta is done by stages : provide warning both verbally and in writing, do rescheduling and reconditioning, carry out the deliberation familial, through by BASYARNAS institutions and carry out the execution to the collateral with applicable laws and regulations.